A conceptual model of the relationship between personal values and personal tax culture regarding the perception of tax system fairness - Aleksandra Vehovar; Damijan Mumel; Lidija Hauptman (Naše gospodarstvo / Our Economy, 2018)
The purpose of this paper is to explore the relationship between personal values and personal tax culture regarding the perception of a tax system's fairness. The paper deals with the main theoretical starting points of the fundamental cornerstones of the general tax culture such as tax evasion, tax compliance and tax system. Based on findings in Schwartz's model of personal values, the paper discusses some of individual personal values, categorized into ten groups within a two-dimensional circular design, along two bipolar dimensions. Because this field of research is largely unexplored and based on the previous theoretical research, a conceptual model for analysing this relationship was developed.
Keywords: M41; M48; M26; 330; personal values; personal tax culture; tax system; tax compliance; conceptual model